IMPLEMENTASI PENATAAN DAN PEMBINAAN PUSAT PERBELANJAAN DAN TOKO SWALAYAN OLEH DINAS PERDAGANGAN KOPERASI DAN USAHA MIKRO KABUPATEN PONOROGO - Niswandri Prasojo, Andri; Nurati, Dian Esti; Purwanto, Adi (JI@P, 2020)
This study aims to describe and analyze how the implementation of structuring and guiding shopping centers and convenience stores by Trade Cooperatives and Micro Enterprises office of Ponorogo Regency along with what are the supporting factors and obstacles to its implementation. This type of research is qualitative research using the theory of George C. Edward III as a basis for thinking in assessing the implementation of policies that are influenced by 4 main variables namely communication, resources, disposition, and bureaucratic structure. The method of data collection is done by observation, interviews, and documentation. The results showed that the implementation has not been running optimally. Communication is good enough. Resources are not optimal, the number of staff and supporting facilities for implementation are still inadequate. Disposition, the selection of personnel is appropriate, but there is no incentive. Bureaucratic Structure is not optimal yet the absence of Regional Regulations or Regents Regulations affecting Standard Operating Procedures (SOPs) and fragmentation between work units involved in the implementation process.